Life in an endemic COVID-19: Older adults' well-being, activity, and perceptions - NGU, Rachel (Institutional Knowledge at Singapore Management University, 2022)
The current research brief provides a preliminary examination of whether older adults have been able to ‘return’ to the pre-pandemic way of life in an endemic COVID-19. To do this, we look at several key indicators, including (1) tracking older adults’ overall life satisfaction, activity levels, and trust in government over the past 3 years, (2) older adults’ confidence to resume activities, as well as subjective perceptions about their safety when leaving the home in an endemic COVID-19, and (3) older adults’ ability to adhere to the Home Recovery Program (HRP), where individuals with COVID-19 are able to recover from the virus at home rather than in an isolation facility. We make use of data from the Singapore Life Panel®, with an average of 7078 respondents participating across all months of data utilized for our analysis. The following recommendation were made: (1) Greater assurances should be provided to older adults about the safety of the resumption of activities, especially for older adults greater in age, and who are less educated. (2) The level of trust that respondents have in the government’s response to COVID-19 is found to be an important factor shaping the confidence that respondents have in participating in activities with an endemic COVID-19, as well as how safe they feel from COVID-19 when leaving the house. (3) Greater support for less educated respondents were more likely to find it difficult to adhere to the HRP.